The Effect of Dietary Tarragon (Artemisia Dracunculus) Powders in Different Levels on Carcass Characteristics and Some Internal Organ’s Weight of Broiler Chickens - Yildirim,F (2018)
ABSTRACT This study was conducted to investigate the effects of different levels of Tarragon powder on head, chicken feet, some internal organs and carcass characteristics of broiler chickens. One day -old two hundred forty Ross 308 male broilers were randomly allocated into four treatments and six replicates per treatment. At each replicate ten birds were used. All birds at 42 days had ad libitum access to water and feed and were exposed to a 23L:1D lighting program. The diets were set on the basis of corn, soybean and wheat meal, formulated according to the recommendations of the Ross 308 manual (starter days 1-14, grower days 15-37, and finisher days 38-42), and offered as mash. The tarragon plant used in the research was purchased from a vegetable market in Erzurum province in Turkey. Treatments were: base diet (Control), base diet + 0.1% of Tarragon powder (group A), base diet + 0.2% of Tarragon powder (group B), base diet + 0.5% of Tarragon powder (group C). Except for relative wing and head weight, other carcass traits were not significantly affected (p>0.05) by different levels of Tarragon powder. The lowest relative head weight (p<0.001), and the highest relative wing weight (p<0.05) were observed in the control group. The results of this study suggest that the addition of Tarragon powder to broiler diets has no effect on other important carcass traits, except for the head and wing weights of broiler chickens.